A compact ultra‐wideband bandpass filter with good selectivity based on interdigital coupled‐line. Issue 9 (17th May 2018) - Xia, Xinlin; Chen, Fengjun; Cheng, Xu; Deng, Xianjin
Abstract: In this article, a compact ultra‐wideband (UWB) bandpass filter (BPF) with sharp selectivity using interdigital coupled‐line is proposed. Its input signal propagates through two different signal paths. The main transmission path consists of two coupled‐line line structures, and the other signal path is a microstrip loaded by two short‐circuited stubs. Comparing with some other UWB filters based on interdigital coupling three lines, the selectivity of the proposed filter is significantly improved due to the two transmission zeros located at the lower and upper edge of the passband separately. Moreover, its transmission zeros are analyzed by ABCD parameter matrix. A prototype of the proposed filter is fabricated and measured, the results show that the proposed filter achieve a bandwidth of 126% from 2.95 to 13.05 GHz, and a size reduction of 37.3% compared to the former UWB BPF with similar structure. Besides, the proposed filter can offer some other advantages such as good return loss, low insertion loss, compact size(0.48λg × 0.08λg), and stable group delay at UWB frequencies. This filter can be a good candidate for ultra‐wideband applications.